ANALISIS KENERJA KEUANGAN PADA PT. MATAHARI DEPARTEMENT STORE Tbk DI BURSA EFEK INDONESIA - Murnawati¹, Lili Erti², Tasril³ (Universitas Lancang Kuning, 2025)
The clothing industry does not always experience an increase, there are times when it experiences a decline, the community economy has a very big influence on people's purchasing power, especially in the clothing industry, with the Covid-19 pandemic, people's behavior has changed to be more focused on technology, where there has been a shift in people's shopping patterns from shopping from modern stores to virtual stores, this is quite a big challenge for retail companies, Matahari Department stores are also affected according to box data in 2019, they had 169 outlets in 2020, there were 147 outlets in 2020. 2021 until now has 148 outlets. The aim of the research is to determine the financial performance of PT. Matahari Department Store tbk, The population in the research is the financial report of PT. Matahari Department Store, Tbk The research uses Discritif, Qualitative, Financial Ratio Analysis methods which use Liquidity, Solvency and Profitability Ratios. The research results for Liquidity ratios are Current Ratio in the poor category 69.71 < 200% while for the Quik Ratio it is 39.68 % < 150% is in the poor category while the solvency ratio is Debt to Asset Ratio and Debt to Equity Ratio Exceeds industry standards in the unfavorable category while the NPM and ROA ratios are below industry standards in the Unfavorable Category.